Influencia del aumento de la Remuneración Mínima Vital en la gestión financiera de la empresa Servicio Médico Complementario S.A.C, distrito de Trujillo, año 2018 - Esquivel Urtecho, Abelardo Ramiro (2019)
The fundamental purpose of this research is to determine the influence of the increase of the Minimum Vital Compensation in the financial management of the company Complementary Medical Service I.N.C., in order to perform an analysis before and after the increase in the minimum vital remuneration, and thus determine the incidence generated by this action and to be able to provide timely information for decision making. To carry out the present investigation, the company was taken as a population and shows the Company Complementary Medical Service I.N.C. Trujillo district, which through the documentary compilation, the relevant financial analysis was carried out, which shows that the result of the remunerative increase causes the company to cross a deficit in its liquidity, bringing with it a malaise in the financial management of the company, reflected in its profits. It is also important to note that the design of this research is nonexperimental. When analyzing the financial situation of the year 2018 of the company Complementary Medical Service I.N.C., it is observed that although there was an overwhelming growth in sales that generated a greater number of accounts receivable commercial third parties; Liquidity for this year was lower, bearing in mind that activity was maintained throughout the year in exercise; with this we deduce that the increase in minimum remuneration caused instability in financial management processes that directly affect their liquidity since the aforementioned increase was not foreseen. Therefore, it has been determined that the increase in minimum remuneration has a negative impact on the financial management of the company of Complementary Medical Service I.N.C. because even having worked all the 2018 period, the generated profit is lower than projected for that year, keeping in mind that the aforementioned projection was based on the 6 months worked in the predecessor period 2017. Thus the present investigation reveals that Implementing a plan that contains management proposals and projected financial information will help facilitate decision making in an appropriate manner and at the right time and thus the company is prepared for contingencies or unforeseen future changes.